A Method to Reduce the Algorithm Complexity of the Single-Photodiode-per-Polarization Coherent Receiver - Zhou, Keji; Cui, Sheng; Tu, Yicong; Liu, Deming (IEEE photonics journal, 2020)
Single-photodiode-per-polarization coherent receivers (SCRs) can preserve all of the merits of the conventional digital coherent receivers (DCRs) such as supporting chromatic dispersion (CD) compensation and polarization multiplexing, whilst have much lower optical complexity. But the overall algorithm complexity of the SCRs is relatively higher because an extra dedicated field reconstruction algorithm (FRA) is required in addition to the standard algorithms used in DCRs. The heavy computation burden introduced by the FRA poses a major obstacle to reduce the DSP chip size and power consumption. In this paper we propose a method to reduce the overall algorithm complexity of the SCR by utilizing several techniques, including utilizing a strong local oscillator (LO) to mitigate the signal-signal beat interference (SSBI), a pseudo-single-side-band signal to recovery the signal field and a new FRA to reuse the operations in the CD compensation algorithm to realize field reconstruction. Other than reducing the overall algorithm complexity, the new method also make the SCR more robust to laser frequency offset compared with the existing heterodyne detection based FRA. Numerical simulations and experiments are presented to demonstrate the merits of new method with respect to the existing ones.